Kearifan Lokal dalam Perspektif Ekonomi pada Tradisi Pernikahan Masyarakat Kerasi Desa Kuala Behe - Heni Kuswanti; Herkulana; Jumardi Budiman (Ekuitas: Jurnal Pendidikan Ekonomi, 2022)
The purpose of this study was to determine local wisdom from an economic perspective on the marriage tradition of the Kerasi community, Kuala Behe ​​Village. This research was conducted using the phenomenological method.  The sampling technique used purposive sampling technique by setting two criteria on the research informants.  Data collection techniques were carried out by in-depth interviews, observation and documentation of the wedding committee book records. Data analysis was carried out with data analysis steps, namely collecting data, reducing data, presenting data and concluding or verifying.  The validity of the data was checked by method triangulation and source triangulation.  Method triangulation is done by collecting data through interviews, observation and documentation. Meanwhile, source triangulation is taken by comparing the data received from various selected sources of informants. The results showed that local wisdom in an economic perspective on the marriage tradition of the Kerasi community, Kuala Behe ​​Village, was the establishment of a tradition of providing 3 types of material assistance to the wedding ceremony.  The forms of assistance are in the form of andelan, pembanto’ and amplop.  This tradition is an ancestral tradition that has been adapted to the needs of today's society.  This tradition is a form of mutual assistance between community members which aims to ease the financial burden of the implementer of the marriage.  Although the aim is mutual cooperation, this tradition also contains a reciprocal value, namely the commitment of all community members to provide assistance with the same value to people who have provided assistance to them.  This existing tradition is a hallmark of the Malay community and will not be completely the same as other regional communities.